2003
DOI: 10.1034/j.1600-0714.2003.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of AgNOR counts in diagnosing epithelial dysplasia

Abstract: Mean AgNOR count can be a useful tool in definitive diagnosis of epithelial dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
(25 reference statements)
2
18
0
2
Order By: Relevance
“…Our results reaffirm the finding of previous studies, 32,33 that is, an increase in AgNOR counts in dysplastic leukoplakia, compared with non‐dysplastic leukoplakia and NOM. Thus, the AgNOR might be quantitative, discriminative, and easy to monitor routinely in detecting incipient cellular alterations 34 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results reaffirm the finding of previous studies, 32,33 that is, an increase in AgNOR counts in dysplastic leukoplakia, compared with non‐dysplastic leukoplakia and NOM. Thus, the AgNOR might be quantitative, discriminative, and easy to monitor routinely in detecting incipient cellular alterations 34 .…”
Section: Discussionsupporting
confidence: 92%
“…Ray et al in their studies on premalignant lesions showed higher mean AgNOR counts in leukoplakia as compared to normal epithelium, [10] which was similar to our study which showed increase in mean AgNOR counts from mild to severe epithelial dysplasia in various leukoplakic lesions. Warnakulasuriya and Johnson also revealed more dispersed counts of AgNOR in all types of dysplasias.…”
Section: Discussionsupporting
confidence: 92%
“…AgNOR have been shown to be replicatory markers. Mean AgNOR count can be useful in diagnosing histological features representing oral leukoplakia and has been shown to correlate with clinical outcomes of various cancers [10]. An obvious feature of all oral cancers is excessive proliferation of oral keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Xie et al (17), the quantitative analysis of NORs may help distinguish a normal epithelium from epithelial dysplasia and oral squamous cell carcinoma. In fact, for Ray et al (18), the quantative analysis of NORs is a useful tool for the definitive diagnosis of epithelial dysplasia. However, according to Elangovan et al (2008) (6), the quantative analysis of NORs is proportional to the cell proliferation rate and not necessarily indicates the malignant transformation potential of a specific lesion, but the morphologic characteristic of NORs may be an important tool in the attempt of differencing hyperplasic, pre-malignant and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%